Coated tool parts and coating methods
The coating for machining tool parts addresses the issues of defect density and adhesion by using a specific layered structure with varying Al and Si content, achieving high hardness and wear resistance and extending tool life.
Patent Information
- Application Number
- JP2024557229
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-05-31
- Filing Date
- 2023-05-10
- Publication Date
- 2025-04-30
- Estimated Expiration
- 2043-05-10
AI Technical Summary
Existing coatings for machining tool parts with high Al content often have high defect density or poor adhesion, leading to reduced hardness and wear resistance, and are prone to early material failure.
A coating structure comprising a bonding layer and a wear layer, each with multiple sublayers of specific individual plies with varying Al and Si content, arranged in a regular alternating pattern to achieve a cubic structure and enhance hardness and wear resistance.
The coating achieves high hardness and wear resistance, with a cubic structure that stabilizes the hexagonal phases in the second and third individual plies, resulting in improved tool life and performance under dynamic stress.
Smart Images

Figure 2025513736000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a coated tool part of a machining tool.The present invention further relates to a method for coating a tool part of a machining tool. [Background technology]
[0002] The tool parts and machining tools can be, for example, tool parts and tools, respectively, used in the metal processing industry. In principle, however, such tools can also be used for processing other materials, for example glass, plastics, etc.
[0003] Machining tools are, for example, turning tools, milling tools, drilling tools, power skiving tools, etc. According to the invention, the coated tool part is part of such a machining tool, which is either constructed as a separate part, for example a cutting insert, or is part of the tool integrated with the tool holder or the tool shaft.
[0004] According to the invention, the coated tool parts are preferably made of cemented carbide, cermet, polycrystalline cubic boron nitride, polycrystalline diamond, cutting ceramics or high speed steel. The abovementioned materials thus serve as substrates for the coating.
[0005] The above-mentioned materials already have very good machining properties, but since they have very high hardness, wear resistance and fracture resistance, in order to optimize the machining properties, tool parts of machining tools or entire machining tools are increasingly coated. Such coatings provide optimal protection for the tool parts or tools in the presence of dynamic stresses due to high cutting speeds and lack of cooling. It is therefore possible to clearly extend the service life of such machining tools with suitable coatings.
[0006] In the prior art, several different coatings have already been disclosed. In this regard, reference is made purely by way of example to US Pat. No. 5,999,623, US Pat. No. 5,999,636. The three aforementioned publications disclose various AlCrSiN coatings. Coatings known from US Pat. No. 5,999,623 are, for example, arc-PVD coatings. Such arc-PVD coatings have a high defect density, which often leads to premature material failure. In contrast, DC-sputtered layers are often too soft and / or have insufficient layer adhesion due to a relatively low ionization.
[0007] Al-containing layers are very problematic as they form a hexagonal phase (hexagonal crystal structure) even at low Al contents, reducing the hardness and wear resistance of the coating. In contrast, more desirable would be an Al-containing coating with a cubic crystal structure. However, the latter is hardly achievable at relatively high Al contents. [Prior art documents] [Patent documents]
[0008] [Patent Document 1] European Patent No. 2310594 [Patent Document 2] European Patent No. 1422311 [Patent Document 3] European Patent No. 2336382 DISCLOSURE OF THEINVENTION [Problem to be solved by the invention]
[0009] It is therefore an object of the present invention to provide a coating for tool parts of machining tools which has a relatively high Al content but nevertheless has a cubic crystal structure and therefore has very high hardness and high wear resistance. [Means for solving the problem]
[0010] This object is achieved by the coated tool part according to claim 1, the tool part comprising a substrate coated with a wear layer and an intermediate layer arranged between the substrate and the wear layer, the wear layer and the intermediate layer each having a plurality of sub-layers arranged one above the other, each sub-layer comprising a first individual ply, a second individual ply, and a third individual ply, the three individual plies within the plurality of sub-layers being arranged regularly and alternately one above the other, the first individual ply comprising Al x1 Me 1-x1 (N y1 C 1-y1 ), the second individual ply comprising Al x2 Me 1-x2 (N y2 C 1-y2 ), the third individual ply comprising Al x3 Me 1-x3-z3 Si z3 (Ny3C 1-y3 ), where 0 ≦ x1 ≦ 0.55 and x1 < x2, x1 < x3 and 0 ≦ y1, y2, y3 ≦ 1, Me comprising at least one of the following elements: Sc, Y, La, Ti, Zr, Hf, V, Nb, Ta, Cr, Mo, W, the ply thickness of the third individual ply comprised in the intermediate layer varying from sub-layer to sub-layer, such that the ply thickness of the third individual ply in a further lower sub-layer closer to the substrate is thinner than the ply thickness of the third individual ply in a further upper sub-layer further away from the substrate, and the ply thickness of the third individual ply comprised in the wear layer being essentially constant from sub-layer to sub-layer or at least varying less from sub-layer to sub-layer than in the intermediate layer.
[0011] This object consists of - providing a tool part functioning as a substrate, - coating the substrate with an intermediate layer, - coating the substrate coated with the intermediate layer with a wear layer and The coating of the substrate by the bonding layer and the coating of the substrate coated with the bonding layer each include the deposition of a plurality of sub-layers arranged one above the other, each sub-layer including a first individual ply, a second individual ply, and a third individual ply, and the three individual plies within the plurality of sub-layers being regularly and alternately arranged one above the other, the first individual ply being Al x1 Me 1-x1 (N y1 C 1-y1 ) and the second individual ply being Al x2 Me 1-x2 (N y2 C 1-y2 ) and the third individual ply being Al x3 Me 1-x3-z3 Si z3 (Ny3C 1-y3 ) where 0 ≦ x1 ≦ 0.55 and x1 < x2, x1 < x3 and 0 ≦ y1, y2, y3 ≦ 1, Me includes at least one of the following elements: Sc, Y, La, Ti, Zr, Hf, V, Nb, Ta, Cr, Mo, W, and the ply thickness of the third individual ply included in the bonding layer varies from sub-layer to sub-layer, whereby the ply thickness of the third individual ply in the sub-layer located further down and closer to the substrate is thinner than the ply thickness of the third individual ply in the sub-layer located further up and further away from the substrate, and the ply thickness of the third individual ply included in the wear layer is essentially constant from sub-layer to sub-layer or at least does not vary as much from sub-layer to sub-layer as compared to the bonding layer, which is also achieved by the method according to claim 14.
[0012] Thus, the coating according to the invention includes a bonding layer and a wear layer arranged on top. Each layer consists of a plurality of sub-layers, and each sub-layer has at least three different individual plies, which in this context are referred to as "first individual ply", "second individual ply" and "third individual ply". In principle, each sub-layer may also have more than three individual plies.
[0013] The three individual plies referred to in the different sublayers have different material compositions (see below for further details). The three individual plies referred to in the multiple sublayers are arranged one above the other in a regular alternating manner in both the bonding layer and the wear layer. The order of the individual plies in the bonding layer may be, but is not required to be, the same order as in the wear layer. It is further noted that the nomenclature "first, second, and third individual plies" used in this context does not imply a required order, but is merely intended to distinguish between the three individual plies.
[0014] For simplicity, the first individual ply is referred to as "1," the second individual ply as "2," and the third individual ply as "3," where sequences such as 123123123... or 213213213... or 321321321... or 123412341234... are possible in the bonding and / or wear layers, where the "4" represents one or more further individual plies per sub-layer.
[0015] The first individual ply is Al x1 Me 1-x1 (Ny1C 1-y1 ), where 0≦x1≦0.55 and 0≦y1≦1, and Me comprises at least one of the following elements: Sc, Y, La, Ti, Zr, Hf, V, Nb, Ta, Cr, Mo, W. Since x1 can also be 0, this means that the first individual ply does not necessarily have to comprise aluminum, but may comprise “only” one of the above-mentioned metals Me. However, preferably, the first individual ply comprises both aluminum and one of these metals. However, there is relatively little Al. Since y1 can vary between 0 and 1, the first individual ply can be a nitride, a carbide or a carbonitride.
[0016] The situation is similar with regard to the composition of the second and third individual plies, the second individual ply being Al x2 Me 1-x2and necessarily has a higher Al content than the first individual ply due to the fact that x1 is less than x2. It is also possible for the second individual ply to comprise nitrides, carbides or carbonitrides, since 0≦y2≦1.
[0017] Third individual ply Al x3 Me 1-x3-z3 S z3 (Ny3C 1-y3 ), the substance mixture comprises, in addition to aluminum and the further metal, also Si. This substance mixture may also take the form of a nitride, carbide or carbonitride (0≦y3≦1). The Al content of the third individual ply is higher than the Al content of the first individual ply, but not necessarily higher than the Al content of the second individual ply.
[0018] It should be noted that the molar ratios of the three individual plies specified herein are each reported as a decimal in absolute value, such that, for example, a molar ratio of 0.55 corresponds to a molar ratio at 55% atomic percent (55 at%).
[0019] The specified material composition of the three individual plies, and their alternation one above the other, offers various technical advantages. The first individual ply has a relatively low Al content (<55 at%). It may also have a completely Al-free configuration. In combination with one or more of the above-mentioned metals Me, the substance mixture contained in the first individual ply has a cubic crystal structure. The inclusion of cubic nitrides (e.g. CrN, TiN...) or cubic carbides (e.g. TiC, ZrC...) makes it possible to produce cubic solid solutions with much higher hardness and higher wear resistance compared to pure aluminum nitrides or aluminum carbides, which typically have a hexagonal crystal structure.
[0020] The same principle involving cubic nitrides or cubic carbides is also applicable to the second individual ply. However, due to the higher Al content of the second individual ply, the substance mixture present therein actually has a hexagonal structure. However, due to the alternation of the above-mentioned individual plies, the second individual ply is cubically "stabilized" by the first individual ply so that it also has a cubic structure in the end. The second individual ply therefore also advantageously contributes to a higher hardness and a higher wear resistance. The relatively high Al content of the second individual ply results not only in a high hardness but also in a high oxidation resistance.
[0021] The silicon nitride or silicon carbide contained in the third individual ply also increases the hardness of the coating. However, silicon nitride or silicon carbide also typically promotes the formation of a hexagonal crystal structure. However, the cubic crystal structure of the first individual ply inhibits the hexagonal crystal structure of the third individual ply as well. Thus, the actual hexagonal crystal structure of the third individual ply is also "cubically stabilized" by the first individual ply.
[0022] In summary, this means that the hexagonal phase that normally occurs in the second and third individual plies due to their material composition is suppressed by the application of a low-Al first individual ply arranged between them and containing cubic nitrides or cubic carbides. The cubic structure of the first individual ply thus ultimately leads to a cubic structure of the second and third individual plies as well. This has been found to be extremely advantageous.
[0023] A further feature of the coating according to the invention is that the ply thickness of the third individual ply varies from sub-layer to sub-layer within the bonding layer. The ply thickness of the third individual ply preferably increases from bottom to top. However, the increase does not have to be exactly constant, which can hardly be guaranteed in any case for process-related reasons. What is important is that the ply thickness of the third individual ply at least tends to increase from bottom to top, which means that the ply thickness of the third individual ply in at least one sub-layer arranged further down, closer to the substrate, is thinner than the ply thickness of the third individual ply in at least one sub-layer arranged further up, further away from the substrate.
[0024] In the wear layer, the ply thickness of the third individual ply does not vary significantly from the bond layer. The ply thickness of the third individual ply included in the wear layer is preferably essentially constant (constant with processing related variations).
[0025] Thus, there is no "sharp" transition between the individual plies of the bond layer and the individual plies of the wear layer. Instead, there is a sort of Si gradient that rises from bottom to top within the bond layer. As a result, the entire coating is Si-containing and therefore harder than a comparable coating with a non-Si-containing bond layer.
[0026] The coating according to the invention can in particular be produced by high energy impulse magnetron sputtering (HiPIMS). Production by HiPIMS at very high pulse powers produces very dense and low defect layers.
[0027] This achieves the above objective.
[0028] In a refinement of the invention, 0.55≦x2≦0.7, 0.4≦x3≦0.7. In other words, the Al-content of the second individual ply preferably varies between 0.55 and 0.7, and the Al-content of the third individual ply preferably varies between 0.4 and 0.7. These Al-contents have been found to be advantageous in tests carried out by the Applicant.
[0029] In particularly preferred refinements, 0.3≦x1≦0.55 and 0.55≦x2≦0.65 and 0.5≦x3≦0.65.
[0030] In a further refinement, 0.01≦z3≦0.15 is preferably applicable for the third individual ply. The Si content therefore preferably varies between 1% and 15%.
[0031] It has been found to be particularly advantageous to include Cr as metal (Me) in three individual plies. Particularly good test results have been achieved by including chromium nitride in three individual plies (Me=Cr, y1=1, y2=1, y3=1).
[0032] As already mentioned, the ply thickness of the third individual ply included in the bonding layer preferably increases monotonically from sublayer to sublayer as the distance from the substrate increases. This results in a "perfect" gradient progression of the Si content in the bonding layer. However, due to manufacturing-related rotation of the tool parts during coating, there may be variations in the thickness of the individual plies, and therefore, in practice, the increase can only be described as "essentially constant" or at least "having an increasing trend".
[0033] The ply thicknesses of the first, second and third individual plies in the wear layer are preferably constant or at least essentially constant / similar. In a preferred refinement, the ply thicknesses t wear The following are applicable to: 1 nm ≤ t wear ≦200 nm, preferably 1 nm≦t wear ≦30 nm, more preferably 2 nm≦t wear ≦25nm.
[0034] In the depth direction, where the sublayers are arranged one above the other, this results in more than 3 sublayers per micrometer in the bonding layer and the wear layer, respectively, preferably more than 10 sublayers per micrometer, more preferably more than 20 sublayers per micrometer.
[0035] The total thickness of the bonding layer is preferably less than the thickness of the wear layer.
[0036] It will be clear that the features mentioned above and those which will be described hereinafter can be used not only in the specific combination specified, but also in other combinations or alone, without departing from the scope of the invention, and it will be clear that the features mentioned above and those defined in the claims for the coated tool parts also relate in the same or equivalent way to the method according to the invention. [Brief description of the drawings]
[0037] [Figure 1] FIG. 1 is a schematic diagram of a coated tool part according to one embodiment of the present invention. [Diagram 2] FIG. 2 is a schematic diagram for explaining the layer structure of a coating according to one embodiment of the present invention. [Diagram 3] FIG. 1 is a schematic diagram of a test setup for the production of a coating according to one embodiment of the present invention. [Figure 4] FIG. [Diagram 5] 1 is an optical microscope image of a cratered crushed sample of a substrate coated with a coating according to the present invention. [Figure 6] 1 is a SEM image of a substrate coated with a coating according to the present invention. [Figure 7] This is the result of XRD analysis. [Figure 8] 1 is a table of experimental results for different coating variants. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0038] Embodiments of the present invention are presented in the accompanying drawings and explained in detail in the following description.
[0039] 1 shows, in purely schematic form, a coated tool part, the entirety of which is designated by the reference numeral 10.
[0040] The coated tool part 10 may be, for example, a cutting insert. In this embodiment, the coated tool part 10 comprises a substrate 12 made of cemented carbide, the upper surface of which is coated with a coating 14. Of course, it is also possible that the entire surface of the tool part 10 is coated.
[0041] In this case, the coated surface may be, for example, the rake face 16 of a cutting insert that includes one or more cutting edges 18 .
[0042] 2 shows a schematic of the layer structure of coating 14. Coating 14 is divided into an adhesive layer 20 and a wear layer 22. Adhesive layer 20 is bonded directly to substrate 12. Wear layer 22 is applied on top of adhesive layer 20.
[0043] The bonding layer 20 and the wear layer 22 each have a number of sub-layers 24. In this case, each of these sub-layers 24 consists of three individual plies 26, 28, 30. In other embodiments (not shown here), there may be additional individual plies for each sub-layer 24.
[0044] The individual plies 26, 28, 30, referred to in the present context as a first individual ply 26, a second individual ply 28, and a third individual ply 30, each have a different material composition, and each of the first individual plies 26, each of the second individual plies 28, and each of the third individual plies 30 have the same material composition. The three individual plies are arranged one above the other in an alternating order, in this case the sequence 123123123... being chosen.
[0045] The first individual plies 26 and the second individual plies 28 in all sublayers 24 preferably have the same thickness. However, the ply thickness of the third individual plies 30 preferably varies within the bonding layer 20 and is of the same size or thickness (i.e., does not vary) within the sublayers 24 of the wear layer 22. In the bonding layer 20, the ply thickness of the third individual plies 30 at least has a tendency to increase from bottom to top, i.e., going from the substrate 12 to the transition to the wear layer 22. It is particularly preferred if the ply thickness of the third individual plies 30 in the bonding layer 20 increases essentially constantly from sublayer 24 to sublayer 24. An "essentially constant" increase means a constant increase with relatively small process-related variations.
[0046] The total thickness of the coating 14 is preferably within the range of 1 to 10 μm. The thickness of the bonding layer 20 is preferably less than the thickness of the wear layer 22. More preferably, the bonding layer 20 has a proportion of 10 to 30% of the total thickness of the coating 14.
[0047] The first and second individual plies 26, 28 preferably have a ply thickness of 1-30 nm. The ply thickness of the third individual ply 30, as previously described, varies within the bonding layer 20. It preferably increases uniformly within the bonding layer 20 from sublayer 24 to sublayer 24 from bottom to top.
[0048] The first individual ply 26 comprises the following material mixture: Al x1 Me 1-x1 (N y1 C 1-y1 The second individual ply 28 comprises the following material mixture: Al x2 Me 1-x2 (N y2 C 1-y2 The third individual ply 30 comprises the following material mixture: Al x3 Me 1-x3-z3 S z3 (Ny3C 1-y3)。The parameters x1, x2, x3, y1, y2, and y3 comply with the conditions of 0 ≦ x1 ≦ 0.55, x1 < x2, x1 < x3, 0 ≦ y1 ≦ 1, 0 ≦ y2 ≦ 1, and 0 ≦ y3 ≦ 1. The metal Me contains at least one of the following elements: Sc, Y, La, Ti, Zr, Hf, V, Nb, Ta, Cr, Mo, and W.
[0049] As shown by the tests conducted by the applicant, when the Al content in the first individual ply 26 is low and cubic nitrides or cubic carbides (MeN or MeC) are added to the second and third individual plies 28, 30, a cubic structure is obtained. By continuously increasing the Si content in the third individual ply 30 of the bonding layer 20, a bonding layer 20 having high hardness with optimal adhesiveness to the substrate 12 has already been achieved. In addition, as a result of this progression of the increase in the Si ratio within the bonding layer 20, there is no sharp transition between the bonding layer 20 and the wear layer 22.
[0050] Therefore, the first individual ply 26 disposed therebetween also has the effect of causing the second and third individual plies 28, 30, which would have had a hexagonal structure based on the material composition (high Al content in the second individual ply 28 and high Al content and additional Si content in the third individual ply 30), to have a cubic structure as well.
[0051] Experiments carried out by the applicant, in which the material composition of the three individual plies 26, 28, 30 was varied, showed that the three-ply sublayer 24 proposed in this invention is clearly advantageous in terms of both hardness and wear resistance. Some of the results of these experiments are summarized in FIG. 8. The material composition of each of the individual plies 26, 28, 30 (herein called "ply 1", "ply 2" and "ply 3") is shown for various layer structures of the sublayer 24. In addition, the first column in each case indicates the basic structure of the sublayer 24 (monolithic, two-ply or three-ply). Furthermore, it is stated whether a hexagonal structure / phase occurs or not. In the last column, the evaluated individual layers are qualitatively rated, with 1 being very good, 2 being good, 3 being satisfactory, 4 being adequate, 5 being unsatisfactory and 6 being unsatisfactory. Unlike in the past, the molar ratios of the material compositions shown in FIG. 8 are not shown in absolute decimal form but as percentages in at%. Nevertheless, they are shown again below as absolute molar ratios in decimal form.
[0052] An advantageous Al-content for the first individual ply 26 has been found to be, in particular, an Al-content of 0≦x1≦0.55. Furthermore, a preferred Al-content for the second individual ply 28 is 0.55≦x2≦0.65, and a preferred Al-content for the third individual ply 30 is 0.5≦x3≦0.65. A Si-content of 0.01≦z3≦0.15 has been found to be desirable / advantageous for the third individual ply 30. The following material compositions have been found to be particularly advantageous for the three individual plies 26, 28, 30, and are reported respectively as (material composition of the first individual ply 26, material composition of the second individual ply 28, material composition of the third individual ply 30): (CrN, Al 0.58 Cr 0.42 N, Al 0.58 Cr 0.34 S 0.08 N);(Al 0.48 Cr 0.52 N, Al 0.58 Cr 0.42 N, Al 0.58 Cr 0.34 S 0.08 N), (TiN, Al 0.67 Ti 0.25 Sc 0.08, Al 0.58 Cr 0.34 S 0.08 N), (Ti 0.82 S 0.18 N, Al 0.59 Ti 0.41 N, Al 0.58 Cr 0.34 S 0.08 N), (Al 0.49 Ti 0.51 N, Al 0.68 Ti 0.32 N, Al 0.59 Ti 0.33 S 0.08 N).
[0053] While FIG. 8 only shows experimental results for nitrides, further results obtained by the applicant not shown here have shown that various carbides with similar properties and molar ratios of Al and Me can also be used in an equivalent manner.
[0054] Figure 3 shows the material composition (Al 0.48 Cr 0.52 N, Al 0.58 Cr 0.42 N, Al 0.58 Cr 0.34 S 0.08 3 shows in schematic form the experimental setup used for the production of the Cr-based coating 14 with a Cr-type impurity (N) coating. For this purpose, a PVD coating setup with sputtering support by the HiPIMS method was used. In this case, the applicant used a CC800-HiPIMS from CemeCon AG. The coating setup used comprises six cathodes, four of which are operated in HiPIMS mode and two in DC mode. The Si-free target used for the deposition of the first and second individual plies 26, 28 is operated in HiPIMS mode (identified as "HP" in FIG. 3). The Si-containing target used for the deposition of the third individual ply 30 is operated in DC mode (identified as "DC" in FIG. 3). Overall, this is therefore a hybrid process.
[0055] For the coating process, the cleaned tool 10 and the substrate 12 are loaded into a coating device. Depending on their diameter, they are charged for 1, 2, 3 or 4 revolutions so that all functional surfaces can be coated.
[0056] To prepare for the coating process, the coating machine creates a high vacuum in the chamber, and the radiant heaters present in it heat the tool up to about 500 ° C. The subsequent plasma etching process cleans the tool surface. For this purpose, a pressure of 200-500 mPa is established in the coating space with the help of noble gases and a plasma is generated. A negative voltage of more than 100 V accelerates the noble gas ions to the tool surface, where they remove impurities.
[0057] The final step before coating is to clean the target surface by short sputtering of the target. For this purpose, with the help of noble gases, a pressure of more than 1000 mPa is generated and the sputtering process is started by applying a negative voltage to the target. During this target cleaning operation, a closed shutter protects the tool from the application of material.
[0058] Following this, the actual coating of the tool or tool part 10 or substrate 12 can take place. For this purpose, with the help of noble gases, a pressure of 300-600 mPa is generated, then reactive gases, nitrogen and / or acetylene, are introduced until a total pressure of 630-1000 mPa is present. In order to form a tight layer structure, up to four of the cathodes used are not operated with a continuous voltage, but rather are supplied with voltage pulses, thus operating in the so-called HiPIMS mode. These HiPIMS pulses have a length of 10-200 μs, preferably 20-100 μs, and are generated 1000-8000 times per second. By supplying the tool with a negative voltage of 40 V-100 V, the generated metal ions are accelerated onto the tool. To start the sputtering process, the cathodes with the silicon-free target are very quickly supplied with a voltage, so that across the cathodes there is an average power of 6000 W-12000 W. In contrast, the voltage across the silicon-containing targets is increased over a period of 10 to 20 minutes, which gradually and continuously increases the average sputtering power of these targets and thus the thickness of the third individual ply 30 of the bonding layer 20, resulting in the described silicon gradient. After this gradient is deposited, all targets are operated at constant power. Rotation of the tool during the coating process results in the nanostructured coating 14.
[0059] After the coating process is complete, the chamber is cooled to below 200° C. before being vented so that the now coated tool can be removed.
[0060] The material composition of the target shown in FIG. 3 corresponds to the material composition shown in the last row of the Cr-based material mixture in FIG. 8. The coating (Al 0.48 Cr 0.52 N, Al 0.58 Cr 0.42 N, Al 0.58 Cr 0.34 S 0.08N) gave by far the best results, as shown in particular by the evaluated service life of the coated tool parts. In FIG. 4 this is illustrated by the service life evaluation of the various coatings, comparing the coating method of the invention (shown at the far right of FIG. 4), a hexagonal structured AlCrN coating and a hexagonal structured AlCrSiN layer. As is evident from this comparison, with the coating according to the invention it was possible to achieve a service life twice as long as with the coating with a hexagonal AlCrN layer and a hexagonal AlCrSiN layer. FIGS. 5 and 6 show the AlCrSiN coating of the invention in optical microscope images and SEM images. These show in particular the substrate 12 and the coating 14 adhering to it. In FIG. 5 the sublayer 24 can be seen. Furthermore, due to the crater crushed sample the surface 32 of the coating 14 is evident.
[0061] XRD analysis performed by applicant, the results of which are shown in FIG. 7, also supports the fact that the crystalline structure of the coating 14 of the present invention does not occur in the hexagonal phase, but is solely cubic. Further XRD analysis imparted a compressive stress of >2.5 GPa. Instrumented indentation testing revealed a hardness of >33 GPa, and a ratio of the indentation hardness HIT to the indentation elastic modulus EIT: HIT 3 / EIT 2 >0.15 (usually even exceeding 0.2).
[0062] The result was therefore very good material properties of the coating 14 of the present invention.
Claims
1. A coated tool part (10) of a machining tool, comprising: A substrate (12) coated with a wear layer (22) and a bonding layer disposed between the substrate (12) and the wear layer (22), the wear layer (22) and the bonding layer (20) each include a plurality of sublayers (24) arranged one above the other; Each sub-layer (24) includes a first individual ply (26), a second individual ply (28), and a third individual ply (30); the three individual plies (26, 28, 30) of the plurality of sublayers (24) are arranged one above the other in a regular alternating manner; The first individual ply (26) is made of Al x1 Me 1-x1 (N y1 C 1-y1 ), The second individual ply (28) is made of Al x2 Me 1-x2 (N y2 C 1-y2 ), The third individual ply (30) is made of Al x3 Me 1-x3-z3 S z3 (New York 3 C 1-y3 ), 0≦x1≦0.55, x1<x2, x1<x3, 0≦y1, y2, y3≦1, Me comprises at least one of the following elements: Sc, Y, La, Ti, Zr, Hf, V, Nb, Ta, Cr, Mo, W; the ply thickness of the third individual ply (30) in the bonding layer (20) varies from sub-layer (24) to sub-layer (24), such that the ply thickness of the third individual ply (30) in a sub-layer (24) disposed further down, closer to the substrate (12), is less than the ply thickness of the third individual ply (30) in a sub-layer (24) disposed further up, further away from the substrate (12); A coated tool part (10) wherein the ply thickness of the third individual ply (30) included in the wear layer (22) is essentially constant from sublayer (24) to sublayer (24), or at least does not vary significantly from sublayer (24) to sublayer (24) as compared to the bonding layer (20).
2. The Al contained in the first individual ply (26) x1 Me 1-x1 (N y1 C 1-y1 ), the Al contained in the second individual ply (28) x2 Me 1-x2 (N y2 C 1-y2 ), and Al contained in the third individual ply (30). x3 Me 1-x3-z3 S z3 (New York 3 C 1-y3 2. The coated tool part of claim 1 , wherein each of said first and second crystals has a cubic crystal structure.
3. 3. The coated tool part according to claim 1 or 2, wherein 0.55≦x2≦0.7 and 0.4≦x3≦0.
7.
4. 3. The coated tool part according to claim 1 or 2, wherein 0≦x1≦0.55, 0.55≦x2≦0.65, and 0.5≦x3≦0.
65.
5. Coated tool part according to any one of claims 1 to 4, wherein 0.01≦z3≦0.
15.
6. A coated tool part according to any one of claims 1 to 5, wherein Me comprises Cr.
7. Coated tool part according to any one of claims 1 to 6, wherein y1=1, y2=1 and y3=1.
8. 8. The coated tool part according to any one of claims 1 to 7, wherein a ply thickness of the third individual ply (30) included in the bonding layer (20) increases monotonically from sub-layer (24) to sub-layer (24) with increasing distance from the substrate (12).
9. The ply thickness t of the first, second and third individual plies (26, 28, 30) included in the wear layer (22) wear In each case, 1 nm ≦ t wear ≦200 nm, preferably 1 nm≦t wear ≦30 nm, more preferably 5 nm≦t wear A coated tool part according to any one of claims 1 to 8, subject to the condition ≦25 nm.
10. 10. The coated tool part according to any one of claims 1 to 9, wherein in a depth direction in which the sublayers (24) are arranged one above the other, there are more than 3 sublayers (24) per μm, preferably more than 10 sublayers (24) per μm, more preferably more than 20 sublayers (24) per μm, in the bonding layer (20) and in the wear layer (22).
11. Coated tool part according to any one of the preceding claims, wherein the bonding layer (20) has a thickness less than the thickness of the wear layer (22).
12. Coated tool part according to any one of the preceding claims, wherein the substrate (12) is a cemented carbide, a cermet, a polycrystalline cubic boron nitride, a polycrystalline diamond, a cutting ceramic or a high speed steel.
13. A tool for machining a workpiece comprising a coated tool part (10) according to any one of the preceding claims.
14. 1. A method for coating a tool part of a machining tool, comprising the steps of: - providing a tool part that serves as a substrate (12); - coating said substrate (12) with a bonding layer (20); - coating said substrate (12) coated with said bonding layer (20) with a wear layer (22); Including, the coating of the substrate (12) with the bonding layer (20) and the coating of the substrate (12) coated with the bonding layer (20) each comprises a stack of a plurality of sublayers (24) arranged one above the other; Each sub-layer (24) includes a first individual ply (26), a second individual ply (28), and a third individual ply (30); the three individual plies (26, 28, 30) of the plurality of sublayers (24) are arranged one above the other in a regular alternating manner; The first individual ply (26) is made of Al x1 Me 1-x1 (N y1 C 1-y1 ), The second individual ply (28) is made of Al x2 Me 1-x2 (N y2 C 1-y2 ), The third individual ply (30) is made of Al x3 Me 1-x3-z3 S z3 (New York 3 C 1-y3 ), 0≦x1≦0.55, x1<x2, x1<x3, 0≦y1, y2, y3≦1, Me comprises at least one of the following elements: Sc, Y, La, Ti, Zr, Hf, V, Nb, Ta, Cr, Mo, W; the ply thickness of the third individual ply (30) in the bonding layer (20) varies from sublayer (24) to sublayer (24), such that the ply thickness of the third individual ply (30) in a sublayer (24) located further down, closer to the substrate (12), is less than the ply thickness of the third individual ply (30) in a sublayer (24) located further up, further away from the substrate (12), and the ply thickness of the third individual ply (30) in the wear layer (22) is essentially constant from sublayer (24) to sublayer (24), or at least varies less significantly from sublayer (24) to sublayer (24) compared to the bonding layer (20).
Citation Information
Patent Citations
Surface coated cutting tool excellent in abnormal damage resistance and abrasion resistance
JP2016026893A
Surface-coated cutting tool and manufacturing method therefor
WO2017169498A1
Hard film and hard film coated tool
EP1422311A2
Surface covering with static control properties
EP2310594A2
Multilayer coated cutting tool
EP2336382A1